Isolation with rubber dam: knowledge, training, and attitudes of final year dental students - Milanović, Milena; Dimitrijević, Maja; Juloski, Jelena; Juloski, Jovana (Vojnosanitetski pregled, 2022)
Background/Aim. Good undergraduate education is necessary to overcome the reluctance of dentists to use the rubber dam (RD). The aim of the study was to assess de-ntal students’ knowledge, training skills, attitudes, and opinions concerning the use of RD in order to isolate an operation field. Methods. A 34-item original questio-nnaire was distributed to 130 final-year students of the Faculty of Dental Medicine, University of Belgrade. The questions were divided into four segments: general info-rmation, RD-related knowledge and training skills, opi-nions and attitudes regarding the use of RD, and opinions on the intended future use of RD. Results. All students confirmed that they had theoretical lessons about RD and that its advantages were pointed out. During practical courses, 34% of students observed RD placement and 10% of them placed RD on their own or with assistance. Most (88%) of the students did not feel capable of using RD on their own. Less than half of the students (38%) believed that adequate isolation of the operating field is po-ssible without RD. Sixty-four percent of students consi-dered that RD was not uncomfortable for the patients. More than half of the students were willing to use RD in their future practice. Almost all of them planned to gain additional postgraduate training with RD. Conclusion. Students have solid theoretical knowledge about RD; they are aware of its importance and have a positive attitude toward RD use. However, their practical training and skills are poor and insufficient for independent RD use in order to isolate an operation field.